Analisis Berpikir Kritis Pada Pembelajaran PKN di Sekolah Dasar - Deden Dicky Dermawan; Panji Maulana (Jurnal Elementaria Edukasia, 2023)
This study aims to explain the importance of training students' critical thinking skills in Civics learning in elementary schools. The method used in this research is literature study. The data obtained are secondary data in scientific articles related to research problems. The data obtained were processed through data reduction, then described scientifically in order to obtain a research conclusion. The results of this study indicate that critical thinking skills in Civics learning are very dependent on the teacher's delivery using a learning model, this is very significant from 17 articles, 9 of which say that critical thinking skills in Civics learning can be trained and conveyed well if the teacher uses the Problem model. Based Learning. Through this model students become more active in learning so that they gain real experience to solve a problem. Thus the use of the Problem Based Learning model in the learning process helps students to train and improve their critical thinking skills.